PENGARUH PELAKSANAAN ETIKA PROFESI DAN KECERDASAN EMOSIONAL TERHADAP PENGAMBILAN KEPUTUSAN BAGI AUDITOR PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA (BPK RI) PERWAKILAN PROVINSI JAMBI PADA MASA PANDEMI COVID-19) - indah; Efandri Agustian; wulandari (JURNAL RISET AKUNTANSI JAMBI, 2022)
A In making decisions, the auditor must use more than one rational consideration, which is based on the implementation of applicable ethics that he understands and makes a fair decision. In addition, education and experience can also improve competence in decision making. This study is used to analyze the effect of implementing professional ethics and emotional intelligence on auditors in making decisions for auditors. This study took a sample of auditors who worked at the Office of the Supreme Audit Agency (BPK) representing Jambi province during the Covid-19 period. The type of data used is primary data with data collection methods, namely indirect interviews by submitting questionnaires. The analytical tool used is multiple regression. as an analysis technique using SPSS version 24 software. The results of this study indicate that: (1) Professional Ethics has a significant effect on Decision Making for Auditors (2) Emotional Intelligence has a Significant effect on Decision Making for Auditors (3) Professional Ethics and Emotional Intelligence have a significant effect on simultaneous and significant towards Decision Making for Auditors.